1984
DOI: 10.1080/09553008414551621
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Weight, DNA, RNA and Protein Content of the Brain after Neutron Irradiation of the 18-day Mouse Embryo

Abstract: Pregnant mice were irradiated with 0.5 Gy fission neutrons on the eighteenth day of their gestation. The average litter size at birth was unchanged but mortality increased 5-6 fold in the first 3 days. The irradiated mice were the same weight as control mice at birth but showed a progressively increasing weight deficiency up to at least 36 days as compared to controls. Brain weight was 37, 45 and 25 per cent less in 2-, 3- and 52-week old irradiated animals, respectively, and the ratio of brain weight to body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, there was not a good correlation between the reduction of the glutaminase activity and that of glutamine utilization, which was decreased by only 21.4%. It is noteworthy that, taking a dry weight/protein ratio equal to 1.3 (Antal et al, 1984), in both control and glutaminase-deficient mice, flux through glutaminase represented only 0.7% and 1.1% (with 5 mmol/L [3-13 C]glutamine) and 0.3% and 0.4% (with 1 mmol/L [3-13 C]glutamine) of the corresponding maximal glutaminase activity measured in brain homogenates of these mice (Gaisler-Salomon et al, 2009). Thus, despite this, our study shows that a reduction of the maximal activity of glutaminase in the brain is accompanied by a reduction of flux through glutaminase.…”
Section: Characteristics Of Glutamine Metabolism In Brain Slices Frommentioning
confidence: 99%
“…However, there was not a good correlation between the reduction of the glutaminase activity and that of glutamine utilization, which was decreased by only 21.4%. It is noteworthy that, taking a dry weight/protein ratio equal to 1.3 (Antal et al, 1984), in both control and glutaminase-deficient mice, flux through glutaminase represented only 0.7% and 1.1% (with 5 mmol/L [3-13 C]glutamine) and 0.3% and 0.4% (with 1 mmol/L [3-13 C]glutamine) of the corresponding maximal glutaminase activity measured in brain homogenates of these mice (Gaisler-Salomon et al, 2009). Thus, despite this, our study shows that a reduction of the maximal activity of glutaminase in the brain is accompanied by a reduction of flux through glutaminase.…”
Section: Characteristics Of Glutamine Metabolism In Brain Slices Frommentioning
confidence: 99%
“…Several studies have demonstrated that prenatal exposure to low-LET radiation induced abnormalities of the developing brain such as cerebral hypoplasia [5][6][7] and neuronal cell death 8,9 , and deceleration of neuronal migration 10,11 in rodents. As for neutrons, Vogel and his colleagues examined the changes of brain in mice prenatally exposed to 0.5 Gy of fission neutrons [12][13][14] , and showed that the body weight and the brain weight decreased induced in the irradiated mice 12,13 . Regarding the mechanism, they showed that the damage to the brain of the fetus after neutron irradiation was mainly due to killing and /or inhibition of the differentiation of neuroblasts 13 , and inhibition of protein synthesis was also observed in the irradiated brain 14 .…”
mentioning
confidence: 99%
“…As for neutrons, Vogel and his colleagues examined the changes of brain in mice prenatally exposed to 0.5 Gy of fission neutrons [12][13][14] , and showed that the body weight and the brain weight decreased induced in the irradiated mice 12,13 . Regarding the mechanism, they showed that the damage to the brain of the fetus after neutron irradiation was mainly due to killing and /or inhibition of the differentiation of neuroblasts 13 , and inhibition of protein synthesis was also observed in the irradiated brain 14 . Although, their studies revealed the important mechanisms concerned in the abnormalities of developing brain induced by prenatal irradiation with neutrons, the dose-response relationships and mechanisms of the biological effects of prenatal exposure to neutrons in comparison with those of low-LET radiation have not yet been clarified.…”
mentioning
confidence: 99%
See 2 more Smart Citations